PENGARUH MODEL STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR IPS SISWA KELAS III - Egi Rovizialdi; Sugiyono Sugiyono; Asmayani Salimi (Universitas Tanjungpura, 2020)
AbstractThe purpose of this study was to analyze the influence of the Student Teams Achievement Division learning method on the learning outcomes of Social Sciences of thrid grade students of Pontianak City 05th Elementary School. The research method used was an experiment, a form of Quasi Experimental type of non equivalent group design. The study population was all thrid grade students of Pontianak City Elementary School of 40 students. The sampling technique uses purposive sampling. The technique used is measurement technique. Data collection tools in the form of multiple choice tests. The results of data analysis are, the average score of the control class post-test is 68,95 and the experiment is 79,25. Based on the results of the t-test calculation obtained by tcount 2.414>ttable 2.016, then Ha is accepted. This shows that there are differences in the learning outcomes of the control class students with the experimental class. Calculation of effect size is 0.77 with medium criteria. The conclusion of this study is that there is the influence of the Student Teams Achievement Division learning method on the learning outcomes of Social Sciences in thrid grade students of Pontianak City 05 Elementary School in the medium category. Keywords: Learning Methods for Student Teams Achievement Division, Learning Outcomes, Social Sciences